Odpowiedź :
Odpowiedź:
[tex]\frac{5}{6}+\frac{1}{3}=\frac{5}{6}+\frac{1\cdot2}{3\cdot2}=\frac{5}{6}+\frac{2}{6}=\frac{7}{6}=1\frac{1}{6}\\\\\frac{1}{6}+\frac{1}{2}=\frac{1}{6}+\frac{1\cdot3}{2\cdot3}=\frac{1}{6}+\frac{3}{6}=\frac{4}{6}=\frac{4:2}{6:2}=\frac{2}{3}\\\\\frac{4}{15}+\frac{9}{20}=\frac{4\cdot4}{15\cdot4}+\frac{9\cdot3}{20\cdot3}=\frac{16}{60}+\frac{27}{60}=\frac{43}{60}\\\\\frac{1}{4}+\frac{7}{12}=\frac{1\cdot3}{4\cdot3}+\frac{7}{12}=\frac{3}{12}+\frac{7}{12}=\frac{10}{12}=\frac{10:2}{12:2}=\frac{5}{6}[/tex]
Odpowiedź:
5/6 + 1/3 = 5/6 + 2/6 = 7/6 = 1 i 1/6
1/6 + 1/2 = 1/6 + 3/6 = 4/6 = 2/3
4/15 + 9/20 = 16/60 + 27/60 = 43/60
1/4 + 7/12 = 3/12 + 7/12 = 10/12 = 5/6